Differences in Spiritual Coping Strategies of Mothers with Autism Children in Developed and Developing Countries: a Qualitative Systematic Review - Diana, Gimanda Nahdiah; Pratiwi, Cesa Septiana; Afrianty, Dina (Universitas Muhammadiyah Surakarta, 2025)
Comprehensive community support is needed to help mothers cope with the psychological, physical, and social challenges of caring for a child with autism. This study aimed to identify differences in mothers' initial responses, spiritual coping strategies that influence psychological well-being, and factors supporting and inhibiting maternal coping in developed and developing countries. A literature search was conducted on EBSCO, PubMed, Wiley, Science Direct, ProQuest, Research Rabbit, and Google Scholar databases from 2014 to 2023, which was screened using Mendeley. Critical appraisal and data mapping were performed with the Joanna Briggs Institute (JBI) checklist for qualitative research and textual evidence. A total of 18 selected studies were analyzed using a narrative approach. The results identified five main themes: (1) acceptance and love in the face of adversity, (2) resilience through emotional turmoil to social and cultural complexities, (3) strength in community and shared experiences, (4) empowerment, and (5) advocacy. The spiritual coping strategies of mothers in developing countries differ from those in developed countries, influenced by social, cultural, and economic contexts. Social support proved crucial for maternal emotional resilience. Education of health workers on culture-based spiritual coping strategies is needed to support maternal well-being. An approach that considers the social, cultural, and economic context will facilitate access to resources, integration of relevant spirituality, and self-empowerment. This aims to improve maternal mental health and create an inclusive environment that supports families, especially mothers of children with autism.